Improve Critical Thinking Skills with Informatics Educational Games - Samin; Gunarhadi; Efendi, Agus (Universitas Pendidikan Ganesha, 2022)
Facing the challenges of the 21st century Critical thinking is one of the main abilities that students must have. The problem of low critical thinking skills is caused by factors in students and learning that does not focus on developing critical thinking skills. This study aims to develop an Informatics educational game with higher order thinking skill (HOTS) questions based on the Berbras competition to improve students' critical thinking skills. The research design used by the ADDIE model consists of the stages of analysis, design, develop, implementation, evaluation. Test the effectiveness of educational games using experimental research with Noneequivalent Control Group Design. The research subjects were 32 students in class VIIA and 33 students in class VIIB. Collecting data using a questionnaire instrument and an essay test. The research data were analyzed using paired samples test, with the data requirements being normally distributed and homogeneous. The results of the normality and homogeneity test of the data, obtained a significance level greater than 0.05 so that the critical thinking ability data is normally distributed and homogeneous. The increase in critical thinking skills from the N-Gain analysis of the experimental class was 0.63 in the medium category and the control class was 0.43 in the medium category. Based on the results of the paired samples test, the value of Sig. (2-tailed) of 0.000 <0.05, it can be concluded that the use of informatics educational games has a significant effect on increasing students' critical thinking skills.